Improvements in Immune Function and Activation with 48-Week Darunavir/Ritonavir-Based Therapy: GRACE Substudy - Tsoukas, Christos (Hindawi Publishing Corporation, 2013)
Objective. During the course of HIV infection, progressive immune deficiency occurs. The aim of this prospective substudy was to evaluate the recovery of functional immunity in a subset of patients from the GRACE (Gender, Race, And Clinical Experience) study treated with a DRV/r-based regimen. Methods. The recovery of functional immunity with a darunavir/ritonavir-based regimen was assessed in a subset of treatment-experienced, HIV-1 infected patients from the GRACE study. Results. 19/32 patients (59%) enrolled in the substudy were virologically suppressed (<50 copies/mL). In these patients, median (range) CD4+ cell count increased from 222 (2, 398) cells/mm(3) at baseline to 398 (119, 812) cells/mm(3) at Week 48. CD8+% decreased significantly from baseline to Week 48 (P = .03). Proliferation of CD4+ lymphocytes in response to CD3+/CD28+, phytohemagglutinin, and pokeweed was significantly increased (P < .01) by Week 12. Proliferation in response to Candida and tetanus was significantly increased by Week 48 (P < .01 and P = .014, resp.). Staphylococcal enterotoxin B-stimulated tumor necrosis factor-alpha and interleukin-2 in CD4+ cells was significantly increased by Week 12 (P = .046) and Week 48 (P < .01), respectively. Conclusions. Darunavir/ritonavir-based therapy demonstrated improvements in CD4+ cell recovery and association with progressive functional immune recovery over 48 weeks. This trial is registered with NCT00381303.